The impact of fidelization on the purchasing decision of the company DoReMi Music, Juliaca, 2024 - Flores Torres, Ines (2025)
Objective: Customer fidelization is a key factor in the business success, as it directly influences consumers' purchasing decision. For this reason, this study it was raised the objective of determine the influence of fidelization on the purchasing decisions of customers of the company DoReMi Music EIRL, located in Juliaca, Peru. Materials and methods: The study presented a data-driven approach with a non-experimental, cross-sectional, and explanatory framework. The sample consisted of 146 of the company's customers, of which 61% men and 39% women, with a higher concentration in the 18-29 age range. The instrument applied for measuring the fidelization was a 15-item multifactor questionnaire, while a previously designed, reliable, and valid questionnaire was used to assess the purchasing decision. Results: The results show that 61.6% of customers presented a medium level of fidelization, and 54.8% a medium level in the purchase decision. Furthermore, a positive and significant correlation was found between fidelization and purchase decision (r = 0.68; p < 0.05). The regression model shows that fidelization explained 53% of the variability in the purchase decision (adjusted R² = 0.53; p < 0.001). Conclusions: The study confirms that fidelization influences a significant in the purchasing decision. Thereby, companies must focus on improving the customer experience to foster loyalty and, therefore, increase the likelihood of purchase. DoReMi Music could benefit when implementing more effective fidelization strategies, based of the service excellence and adaptation of the customer experience.